2008
DOI: 10.1016/j.socscimed.2007.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Religious affiliation and mortality in Northern Ireland: Beyond Catholic and Protestant

Abstract: There has been little recent research in Europe exploring the relationship between religion and health. In Northern Ireland previous analysis has tended to divide the population dichotomously as Catholic and Protestant, ignoring the diversity inherent in the Protestant community. This study used a census-based longitudinal study of the enumerated population with five-years follow-up (covering the period 2001e2006) to examine variation in overall and cause-specific mortality by religious affiliation within Nort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 22 publications
1
19
0
1
Order By: Relevance
“…Tables summarizing the 36 articles that were included are available from the first author [23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59]. Articles were excluded because they overlapped in their study samples with articles that were included [60,61,62,63,64,65,66,67], because they did not include a relevant spirituality/religiosity predictor variable [68,69,70,71,72,73,74,75,76,77,78], or because the outcome was not assessed in terms of mortality [79,80,81]. Table 1 summarizes the detailed characteristics of the 69 studies investigating the effect of religiosity/spirituality on mortality in initially healthy populations that were included in the analysis, and the 22 studies investigating the effect of religiosity/spirituality on mortality in diseased populations.…”
Section: Resultsmentioning
confidence: 99%
“…Tables summarizing the 36 articles that were included are available from the first author [23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59]. Articles were excluded because they overlapped in their study samples with articles that were included [60,61,62,63,64,65,66,67], because they did not include a relevant spirituality/religiosity predictor variable [68,69,70,71,72,73,74,75,76,77,78], or because the outcome was not assessed in terms of mortality [79,80,81]. Table 1 summarizes the detailed characteristics of the 69 studies investigating the effect of religiosity/spirituality on mortality in initially healthy populations that were included in the analysis, and the 22 studies investigating the effect of religiosity/spirituality on mortality in diseased populations.…”
Section: Resultsmentioning
confidence: 99%
“…Personal characteristics were drawn from the census and selected on the basis of known association with either caregiving or volunteering: these include age, gender and marital status (married, never-married, and -as a single group -widowed, separated or divorced). Religious affiliation was included as religiosity has been associated with both volunteering and its effects, and previous analyses suggest higher levels of religiosity amongst more conservative Christians [36,37]: here six groups, including no affiliation, were classified (Table 1) 1 Rateable value had been derived as part of an exercise by central government in 2005 to determine the level of local residential tax levels payable for each household, and this data was combined with housing tenure to produce an eight-fold classification of tenure/capital value: private renting; social renting; and, for owner-occupiers, five categories ranging from less than £75,000 to over £200,000 (see table 1), with an additional category for homes as yet unvalued. …”
Section: Methodsmentioning
confidence: 99%
“…The forthcoming 2011 Census in Northern Ireland will include a question about the date of entry to the country, which will allow better classification of migratory patterns and provide better clues as the origins for the observed patterns of illness. Previous studies have demonstrated a marked geographical segregation along religious and cultural lines (O' Reilly and Rosato, 2008) and it might be useful in future studies to see if migrants, and especially the Scottish born, gravitate to certain areas, as this would help identify areas with higher need and therefore potentially better targeting of public health interventions.…”
Section: Discussionmentioning
confidence: 99%